HUBUNGAN RASIO BLENDING KOPI ARABIKA (Coffea arabica) DAN ROBUSTA (Coffea chanephora) TERHADAP TINGKAT KESUKAAN DAN KANDUNGAN SENYAWA VOLATIL DALAM KOPI - Qatrunnada Hanifah, - (2022)
There are two varieties of coffee that are most widely used in food and beverage products, namely arabica coffee (Coffea arabica) and robusta coffee (Coffea canephora). Arabica and Robusta coffee have different aroma and taste characteristics. Aroma and taste are the keys to the taste of coffee. The aroma is caused by the volatile compounds in coffee. This study aims to determine what volatile compounds are contained in Arabica, Robusta, and their mixtures and to relate them to the panelists' preference level. The method used includes blending between arabica (A) and robusta (R) coffee with a ratio of 100%A, 75%A:25%R, 50%A:50%R, 75%A:25%R, and 100%R , gas chromatography-mass spectroscopy for volatile compound content analysis, and organoleptic test for aroma and taste attributes. In this study, the compounds found in Arabica, Robusta, and all their mixtures include caffeine and pentadecanoic acid. Compounds found in Arabica coffee include alpha turmerone, beta turmerone, AR turmerone, beta sesquiphenandrene, methanol, and acetonitrile. Compounds found in robusta coffee include 2,3-dimethylbenzofuran and 4-ethyl-2-methoxyphenol. The preferred coffee aroma is the aroma of coffee with a ratio of 50%A:50%R. The preferred coffee taste is a mixture of coffee with a ratio of 775%A:25%R. Key words : Aroma, Coffee, Gas Chromatography, Organoleptic, Taste, Volatile Compound